New fluorescein dye derivatives and their use as an efficient photoiniator using blue light LED - Alarcon, Rafael Turra [UNESP]; Gaglieri, Caroline [UNESP]; da Silva, Bruno Henrique Sacoman Torquato [UNESP]; da Silva Filho, Luiz Carlos [UNESP]; Bannach, Gilbert [UNESP] (Elsevier, 2017)
This work investigates the degree of conversion, thermal properties, and morphological features of polymers obtained using UDMA monomer and fluorescein and its derivatives dyes as photoinitiator. Photopolymerization has opened new research and material due to its synthesis ability as well as ecological and economic advantages. Fluorescein is a dye with great fluorescent properties; therefore, it could be used as initiator in photopolymerization, including its derivatives. Simultaneous Termogravimetry-Differential Thermal Analysis and Derivative Thermogravimetric (TG/DTG-DTA), Differential Scanning Calorimetry (DSC), Middle Infrared Spectroscopy (MIR), and Scanning Electronic Microscopy (SEM) were used to determine thermal properties, degree of conversion, and morphological characteristics of polymers obtained. The data show that the use of fluorescein and its derivatives as photoinitiators did not change the thermal stability of the polymer (193.13 ± 7.9 °C); however, the chlorinated dyes produced a better degree of conversion (78.73% to F-2 and 69.36% to F-5) than brominated dyes (21.18% to F-3 and 1.21% to F-6), resulting in solid rigid polymers.